FROM ABSOLUTE DETERMINISM TO THEORY OF COGNITIVE MODIFIABILITY OF REUVEN FEUERSTEIN - INVITATION FOR REFLECTION - Mônica Deorsola Xavier Negri; Liliana Maria Labronici (Universidade Federal do Paraná, 2001)
This study comprises determinisitic view of Laplace based on forcast and control, opposed to the cognitive modication possibility of the human being, considering the Theory of Cognitive Modifiability of Reuven Feuerstein.